Health shocks and households’ vulnerability to poverty in Nigeria: a quasi-experimental analysis - Paul Eze; Chimere O. Iheonu (Health Economics Review)
Abstract Health shocks are a critical driver of poverty in low- and middle-income countries (LMICs). This study investigates the impact of health shocks on household poverty risk in Nigeria and evaluates the protective capacity of existing health insurance mechanisms, using data from the 2023/2024 General Household Survey (n = 4,779 households). We first estimated household vulnerability using Chaudhuri's (2003) Vulnerability as Expected Poverty framework, addressing heteroskedasticity in consumption estimation via feasible generalized least squares. We then modeled the probability of household vulnerability following health shocks using probit regression. Finally, we implemented propensity score matching to isolate the effect of health shocks on households’ vulnerability. Our results indicate that 56.1% and 59.2% of Nigerian households are vulnerable to poverty, using the international ($2.15/day) and national ($2.48/day) poverty lines, respectively. Vulnerable households are more prevalent in northern regions, rural areas, larger households, and poorer households. We found evidence that, based on the international poverty line, health shocks significantly increased the probability of household vulnerability (ATT = 0.053, SE = 0.023) compared to matched households without health shocks, with a slightly higher impact (ATT = 0.054, SE = 0.023) if using the national poverty line. Household size, dependency ratio, household head’s education and employment status, and residence were significant predictors of vulnerability. Despite their potential, health insurance, covering only 2.2% of households, did not offer adequate protection against health shocks. This study provides robust evidence that health shocks increase households' vulnerability to poverty and perpetuate existing poverty. Financial protection measures need to be considered in broader poverty reduction policies.